Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1016/s0006-3495(98)78031-2
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Microspectroscopy of Myeloperoxidase and Cytochrome b558 in Human Neutrophilic Granulocytes

Abstract: With (resonance) Raman microscospectroscopy, it is possible to investigate the chemical constitution of a very small volume (0.5 fl) in a living cell. We have measured resonance Raman spectra in the cytoplasm of living normal, myeloperoxidase (MPO)-deficient, and cytochrome b558-deficient neutrophils and in isolated specific and azurophilic granule fractions, using an excitation wavelength of 413.1 nm. Similar experiments were performed after reduction of the redox centers by the addition of sodium dithionite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
(45 reference statements)
4
49
0
Order By: Relevance
“…For example, Salmaso et al used resonance Raman spectroscopy to study the enzyme eosinophil peroxidase in living immune cells [197]. Sijtsema et al were able to distinguish redox states in single immune cells by measuring resonance Raman signals from cytochrome b 558 and myeloperoxidase [198].…”
Section: Applicationsmentioning
confidence: 99%
“…For example, Salmaso et al used resonance Raman spectroscopy to study the enzyme eosinophil peroxidase in living immune cells [197]. Sijtsema et al were able to distinguish redox states in single immune cells by measuring resonance Raman signals from cytochrome b 558 and myeloperoxidase [198].…”
Section: Applicationsmentioning
confidence: 99%
“…It has been demonstrated that Raman microspectroscopy is capable of imaging cellular organelles such as the nucleus or chromatin, 1,2 mitochondria, 3 and lipid bodies, 4,5 as well as following metabolic processes or enzymatic activity inside cells. [6][7][8] Apart from imaging subcellular features, Raman imaging may provide an opportunity to follow the uptake of molecules in cell cultures. One way to distinguish incorporated molecules inside cells is to use deuterated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Resonant Raman microspectroscopy has also been used to study eosinophyl peroxidase in eosinophilic granulocytes 9 and NADPH oxidase and myeloperoxidase in neutrophilic granulocytes. 10 The temporal changes in the redox state of the enzymes in these leukocytes could also be followed in vivo using resonant Raman scattering. 11 Nonresonant Raman scattering is 3-4 orders of magnitude weaker than resonant Raman scattering.…”
Section: Introductionmentioning
confidence: 99%